Perancangan Ulang Desain UI/UX pada Aplikasi ibisPaint X dengan Penerapan Metode The Wheel - Eka Novianti; Mia Kamayani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Rapid technological developments have made smartphones not only function as communication devices, but can also be used as a place to draw digitally. Mobile-based graphic design applications, namely ibisPaint X. found problems experienced by users, such as difficulty in using the application, features that are difficult to find, and confusing displays. This study uses the wheel method to overcome problems faced by users which has four main stages, namely analysis, design, prototype, and evaluation focusing on user needs analysis, prototype design using figma, and usability testing using a system usability scale to measure the effectiveness of the resulting design. The results of this study showed a score before the redesign of 38.33, far from the minimum average value of the system usability scale of 68. After the redesign, the score increased very well, the score obtained was 82 indicating success in improving user experience and needs. Changes occurred on the login page, main menu, and the presence of a brush type search feature to make it easier for users when using the ibisPaint X application. This study provides a good contribution to the development of the ibisPaint X application in meeting user needs and is expected to be a reference in order to compete in the increasingly advanced digital era.